2016
DOI: 10.1002/pon.4256
|View full text |Cite
|
Sign up to set email alerts
|

Qigong/tai chi for sleep and fatigue in prostate cancer patients undergoing radiotherapy: a randomized controlled trial

Abstract: Objectives Sleep disturbances and fatigue are common in prostate cancer patients undergoing radiotherapy. Prior research suggests mind-body techniques may improve these outcomes. We conducted a randomized-controlled trial of qigong/tai chi (QGTC) in men with prostate cancer undergoing radiotherapy. Methods Men with prostate cancer starting definitive radiation were randomized to one of three groups: (1) QGTC; (2) light exercise (LE); or (3) wait list control (WLC). Sleep disturbances (PSQI) and fatigue (BFI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
117
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(119 citation statements)
references
References 44 publications
1
117
0
1
Order By: Relevance
“…A total of 20 studies met the inclusion criteria; including 19 randomised controlled trials [ 16 , 17 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], and one prospective controlled trial [ 62 ] informed this systematic review. One study included a diet only intervention [ 56 ], three studies included combined diet and exercise interventions [ 16 , 17 , 52 ], and sixteen included exercise only interventions [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 57 , 58 , 59 , 62 ]. Two exercise only interventions were described as two separate studies, both by Galvao et al [ 47 , 48 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 20 studies met the inclusion criteria; including 19 randomised controlled trials [ 16 , 17 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], and one prospective controlled trial [ 62 ] informed this systematic review. One study included a diet only intervention [ 56 ], three studies included combined diet and exercise interventions [ 16 , 17 , 52 ], and sixteen included exercise only interventions [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 53 , 54 , 55 , 57 , 58 , 59 , 62 ]. Two exercise only interventions were described as two separate studies, both by Galvao et al [ 47 , 48 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies specified eligibility criteria and all but four studies [ 17 , 56 , 57 , 62 ] provided point estimates and measures of variability. Despite the generally high methodological quality of the included interventions, an intention to treat approach was either not conducted or adjusted in seven of the 18 interventions [ 17 , 49 , 50 , 52 , 58 , 59 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane Review found that methylphenidate was the only agent that caused a significant, albeit small, improvement in CRF . There are a growing number of studies investigating nonpharmacologic treatments for CRF; for example, data suggest that exercise causes a small to moderate decrease in CRF . The psychosocial interventions studied have reported small but significant reductions in fatigue .…”
Section: Introductionmentioning
confidence: 99%
“…13 There are a growing number of studies investigating nonpharmacologic treatments for CRF; for example, data suggest that exercise causes a small to moderate decrease in CRF. [14][15][16][17][18][19] The psychosocial interventions studied have reported small but significant reductions in fatigue. 14,20,21 Overall, methodology and design challenges continue to limit the impact of this work.…”
Section: Introductionmentioning
confidence: 99%